Peer observation of teaching in an Indonesian higher education contexts: observers’ and observed teachers’ perception / Sri Rejeki Murtiningsih and Nur Azima - Murtiningsih, Sri Rejeki; -, Nur Azima (Universiti Teknologi MARA, 2022)
Teaching in higher education in the Indonesian context has received more attention in the past two decades. Actions have been taken to improve teaching quality. One of the attempts conducted by a department in an Indonesian university is peer observation of teaching. The objectives of this study are twofold. The first objective is to investigate the observers’ and the observed teachers’ perspectives of their participation in a POT. The second objective is to discover the perceived benefits toward their teachers’ professionalism. Two observers and two observed teachers participated in this study. Data were obtained through in-depth interviews. The findings uncovered that the observers and the observed teachers claimed to have improved their pedagogical competence and believed that the institution required further action. The data also revealed the benefits that the observers gained because they could see a teaching model and that the observed teachers received feedback from more experienced teachers. Participants also considered skills in giving and accepting criticism were necessary for their growth and that the POT served them as a moment of self-reflection. The limitation of the study is that it lacks information on the teaching performance upon the POT and peer relationship. The study implies that the institution should follow through the results of the POT.